PROBLEMS OF GENDER INEQUALITY IN FORMING WAGES IN THE REPUBLIC OF KAZAKHSTAN (Journal of Economic Research & Business Administration, 2018)
In this article, problems of wage differentiation by gender and gender segregation in the Republic ofKazakhstan had considered an analysis of factors of wage differentiation between workers and womenhad presented. The reasons for the differences in people’s earnings are complex and contradictory. Thepurpose of this work is to sanctify the theoretical aspects of the differences in wages; conduct a selectivereview of the principles of empirical analysis, which helps establish factors affecting the level of wages;to assess the differences in wages, taking into account the gender aspect. With the help of the earningsfunction, the return on education and the number of years of work experience are determined, at whichthe maximum of the logarithm of earnings for both sexes had reached. The econometric tool used inanalyzing the determinants of wages is not only quantifiable variables, such as the level of education andwork experience, but also dummy variables that allow estimating the differences in salary levels betweenmales and females. The results of the study allowed the authors to establish that the work experience andthe duration of training have the same effect on the logarithm of wages in both men and women. Thedifference in wages between men and women in the Republic of Kazakhstan is due, first, to the distributionof labor between sectors and sectors of the economy.